Performance of worlwide interoperability for microwave access (WIMAX) in non line of sight and mulitipath environment - 246543 Khairul Bariah Abas Azmi (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Kejuruteraan (Elektrik - Elektronik dan Telekomunikasi)) - Universiti Teknologi Malaysia, 2007